225OImpact of radiological disease progression on the health status of patients (pts) with BRCA-mutated advanced ovarian cancer (OC) treated with maintenance olaparib (OL) or placebo (PL) after first-line platinum chemotherapy. (24th November 2019) - Friedlander, M L; Hettle, R; Parkhomenko, E
Abstract: Background: In SOLO1 (NCT01844986), maintenance OL significantly improved progression-free survival vs PL (HR 0.30; 95% CI 0.23–0.41; Moore et al. NEJM 2018) following response to first-line platinum chemotherapy in pts with BRCA-mutated advanced OC. We compared pt health status pre- and post-radiological progression (RECIST) in SOLO1 using the EQ-5D-5L descriptive system and visual analogue scale (VAS). Methods: EQ-5D-5L data were collected at baseline, day 29, every 12 weeks for 3 years, then every 24 weeks until data cut off (May 2018). Using the last EQ-5D-5L pre-progression as baseline, we assessed changes in each domain score, the proportion reporting any problem (levels 2–5) by domain, and Paretian classification of health change (PCHC) at first post-progression EQ-5D-5L. Impact of progression on VAS was assessed by mixed-effects repeated measures analysis. Data were pooled across study arms. Results: 74/100 OL pts and 81/95 PL pts with RECIST progression completed the EQ-5D-5L pre- and post-progression. Pre-progression, any problems were reported in 56%, 54%, 40%, 31% and 5% for anxiety/depression, pain/discomfort, usual activity, mobility, and self care respectively. Post-progression, proportions reporting problems with anxiety/ depression (68%), pain/discomfort (65%) and self care (15%) increased, while usual activity (43%) and mobility (30%) were unchanged. Across all levels, worsening was reported in anxiety/depression (34%), pain/discomfort (27%) and self care (13%). By PCHC, 56% reported worsening in at least one domain, with 37% reporting worse overall health status immediately post-progression. Progression was associated with a statistically significant and meaningful reduction in VAS (-0.0714, P < 0.0001). Conclusions: Radiological progression after response to first-line platinum chemotherapy is associated with worsening health status, with anxiety/depression and pain/discomfort most affected. These results highlight the impact of progression on pts and pt-reported health benefits of delaying progression with maintenance OL. Clinical trial identification: NCT01844986. Editorial acknowledgement: Medical writing assistance was provided by Catherine Risebro, PhD, from Mudskipper Business Ltd, funded by AstraZeneca. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: M.L. Friedlander: Honoraria (self), Honoraria (institution), Advisory / Consultancy: AstraZeneca; Non-remunerated activity/ies, Consulting: AbbVie; Research grant / Funding (institution): Beigene; Advisory / Consultancy: Lilly; Advisory / Consultancy: MSD; Advisory / Consultancy: Takeda. R. Hettle: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. E. Parkhomenko: Honoraria (institution), Advisory / Consultancy, Full / Part-time employment, Employee of Parexel, which has received consultancy fees from AstraZeneca: AstraZeneca.